THE CONCEPT AND CLASSIFICATION OF NATIONALLY AND CULTURALLY SPECIFIC UNITS - Muminov Elyor Turayevich (PEDAGOGS, 2025)
Abstract: Nationally and culturally specific units (NCSUs), sometimes called realia, represent lexical and semantic items deeply embedded in the sociocultural fabric of a community. They include references to material culture, institutions, traditions, and phenomena that often lack direct equivalents in other languages. The translation and study of such units have attracted scholarly attention because they reveal how language mediates cultural identity. This thesis explores the conceptual foundations of NCSUs, reviews major classifications, and evaluates their implications for translation studies. By synthesizing theoretical frameworks and practical typologies, the paper argues that understanding NCSUs is essential not only for accurate translation but also for intercultural communication and cultural preservation.